Reduced peak, but no diurnal variation, in thrombin generation upon melatonin supplementation in tetraplegia - Iversen, Per Ole; Dahm, Anders; Skretting, Grethe; Mowinckel, Marie-Christine; Stranda, Annicke; Østerud, Bjarne; Sandset, Per Morten; Kostovski, Emil (Thrombosis and Haemostasis, 2015)
Tetraplegic patients have increased risk of venous thrombosis despite anti-thrombotic prophylaxis. Moreover, they have blunted plasma variations in melatonin and altered diurnal variation of several haemostatic markers, compared with able-bodied. However, whether healthy individuals and tetraplegic patients, with or without melatonin, display abnormalities in thrombin generation during a 24-hour (h) cycle, is unknown. We therefore used the Calibrated Automated Thrombogram (CAT) assay to examine diurnal variations and the possible role of melatonin in thrombin generation. Six men with long-standing complete tetraplegia were included in a randomised placebo-controlled cross-over study with melatonin supplementation (2 mg, 4 consecutive nights), whereas six healthy, able-bodied men served as controls. Ten plasma samples were collected frequently during a 24-h awake/sleep cycle. No significant diurnal variation of any of the measured CAT indices was detected in the three study groups. Whereas endogenous thrombin potential (ETP) was independent (p > 0.05) of whether the tetraplegic men received melatonin or placebo, melatonin decreased (p = 0.005) peak values in tetraplegia compared with those given placebo. Able-bodied men had lower (p = 0.019) ETP and Lag-Time (p = 0.018) compared with tetraplegics receiving placebo. Neither the Time-to-Peak nor the Start-Tail was affected (p > 0.05) by melatonin in tetraplegia. In conclusion, indices of thrombin generation are not subjected to diurnal variation in healthy able-bodied or tetraplegia, but peak thrombin generation is reduced in tetraplegic men receiving oral melatonin.
Keywords: Diurnal rhythm; haemostasis; melatonin; nervous system; thrombin